Community Information Services: A Study on Information Needs of Rural Community in Shivamogga District - Dharani Kumar, P.; Biradar, B. S. (Journal of Information and Knowledge, 2014)
Present survey constitutes the study of community information services offered by the rural libraries of Shivamogga district. A total of 700 respondents from 14 taluks of the district were interviewed by using a structured questionnaire. Survey highlights that all respondents got enrolled their membership in the library, whereas 53.26% of male respondents made visit to the library every day. Mean value shows that preferable library visiting hour is evening (x = 3.23). Study also highlights that books are the most preferred information sources among the male (62.44%) followed by periodical/magazine (60.40%). In case of female television (57.61%) is the most preferred information channel followed by books (43.80%). After analyzing the mean value of all the category of respondents, farmer and labour community (value ranges between 3.00-3.50) are in top two rankings who seek information on different topics. It is evident from the study that agriculture (53.46%), politics (53.06%) and entertainment (45.10%) are the most favourite subject of reading among the male community, whereas entertainment (56.66%), economic issues (48.09) are the most favourite subject of reading among the female community of Shivamogga district.